Fertility and family planning in a Canadian metropolis - Balakrishnan, T. R.; Allingham, John D; Kantner, John F., 1920-2009 (McGill-Queen's University Press, 1975)
Chapter 3 Timing and Spacing of Births ; Socio-Economic Differences in Age at Marriage and the Timing of Births ; Economic Consequences of Childspacing ; Distribution of Birth Intervals ; Analysis of Childspacing Using Closed and Open Intervals ; Summary.